Microenvironmental Targets in Sarcoma - Ehnman, Monika; Larsson, Olle (Frontiers in Oncology, 2015)
Sarcomas are rare malignant tumors affecting all age groups. They are typically classified according to their resemblance to corresponding normal tissue. Their heterogeneous features, for example in terms of disease-driving genetic aberrations and body location, complicate both disease classification and development of novel treatment regimens. Many years of failure of improved patient outcome in clinical trials has lead to the conclusion that novel targeted therapies are likely needed in combination with current multimodality regimens. Sarcomas have not, in contrast to the common carcinomas, been the subject for larger systematic studies on how tumor behavior relates to characteristics of the tumor microenvironment. There is consequently an urgent need for identifying suitable molecular targets, not only in tumor cells, but also in the tumor microenvironment. This review discusses preclinical and clinical data about potential molecular targets in sarcomas. Studies on targeted therapies involving the tumor microenvironment are prioritized. A greater understanding of the biological context is expected to facilitate more successful design of future clinical trials in sarcoma.